Strategic tools in re- shaping and re- mapping business (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2015)
This papers objective is to present in a short but concise way several strategies managers need to implement in order to be able to understand the forces that influencing their business. Contemporary management need to re- focus from up to down- stream activities and come closer to their customers. Special conditions of the information technology and computers which are prevalent in our contemporary society, like the network effects, need to be taken under vast consideration from managers in order to empower their companys market position.